Ivermectin vs moxidectin for treating Strongyloides stercoralis infection: a systematic review - Cesar Henriquez-Camacho; Jose A. Pérez-Molina; Dora Buonfrate; Paola Rodari; Eduardo Gotuzzo; Benilde Luengo; María Nieves Plana (Parasitology)
The aim was to assess the efficacy of ivermectin vs moxidectin for treating Strongyloides stercoralis infection. Ovid MEDLINE, Embase and Web of Science databases were searched for studies comparing ivermectin and moxidectin from inception to February 2024. The outcomes: elimination of infection or parasitological cure, mortality and serious adverse events. We calculated odds ratios (ORs) with 95% confidence intervals (CIs) for dichotomous data. Heterogeneity was assessed using Chi2 test for statistical heterogeneity and results of the I2 statistic. Two trials met the inclusion criteria that included 821 adult participants. Both studies were conducted in southeast Asia (Cambodia and Laos). Neither trial included immunocompromised patients. The mean age of the participants ranged from 40 to 45 years old, with a similar distribution of males and females. For all participants, S. stercoralis infection was confirmed by Baermann method. The evidence was moderate for parasitological cure rate. Certainty was downgraded by 1 level because of imprecision. Moxidectin was not inferior to ivermectin: OR 0.67, 95% CI 0.36–1.25 (P = 0.21), I2 = 0%, 821 participants. No deaths were reported in either trial. One trial reported mild adverse events. In total, 153/726 (21%) participants had an adverse event. The most reported symptoms were abdominal pain and headache. There is evidence for moderate quality that moxidectin is non-inferior to, and as safe as ivermectin; however, more high-quality and well-designed trials are needed. For patients with some underlying immunosuppressive disorder, or in patients who are very young or very old, current data are insufficient to be recommended.